Physical effects upon whey protein aggregation for nano-coating production - Óscar L. Ramos (2014)
Production of edible nanostructures constitutes a major challenge in food nanotechnology, and has attracted a great deal of interest from several research fields - including (but not limited to) food packaging. Furthermore, whey proteins are increasingly used as nutritional and functional ingredients owing to their important biological, physical and chemical functionalities. Besides their technological and functional characteristics, whey proteins are generally recognized as safe (GRAS). Denaturation and aggregation kinetics behavior of such proteins are of particular relevance toward manufacture of novel nanostructures possessing a number of potential uses. When these processes are properly engineered and controlled, whey proteins may form nanostructures useful as carriers of bioactive compounds (e.g. antimicrobials, antioxidants and nutraceuticals). This review discusses the latest advances in nano-scale phenomena involved in protein thermal aggregation aiming at formation of bio-based nano-coating networks. The extent of aggregation is dependent upon a balance between molecular interactions and environmental factors; therefore, the impact of these conditions is addressed in a critical manner. A particular emphasis is given to the effect of temperature as long as being one of the most critical variables. The application of moderate electric fields (MEF), an emergent approach, as such or combined with conventional heating is considered as it may inhibit/prevent excessive denaturation and aggregation of whey proteins - thus opening new perspectives for development of innovative protein nanostructures (i.e. nanocoatings). A better understanding of the mechanism(s) involved in whey protein denaturation and aggregation is crucial as it conveys information relevant to select methods for manipulating interactions